2007
DOI: 10.1200/jco.2007.25.18_suppl.4000
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase III study of irinotecan and 5-FU/FA with or without cetuximab in the first-line treatment of patients with metastatic colorectal cancer (mCRC): The CRYSTAL trial

Abstract: 4000 Background: Cetuximab in combination with irinotecan-based regimens has proven activity in previously-treated patients (pts) with mCRC. The present trial investigated the effectiveness of cetuximab in combination with standard FOLFIRI compared with FOLFIRI alone in the first-line treatment of pts with epidermal growth factor receptor (EGFR)-expressing mCRC. Methods: Pts were randomized 1:1 to receive either cetuximab (400 mg/m2 initial dose then 250 mg/m2/week [w]) plus FOLFIRI q 2 w (irinotecan 180 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(74 citation statements)
references
References 0 publications
1
70
0
3
Order By: Relevance
“…Several randomized clinical trials have demonstrated superior response rates and progression-free survival times with doublet therapy compared with single-agent fluoropyrimidine therapy [10 -12]. The monoclonal antibodies bevacizumab and cetuximab have contributed further improvements in the response rate and overall survival when combined with chemotherapy [13,14]. A meta-analysis conducted by Grothey et al [15] indicated that patients with advanced CRC received the greatest survival benefit when treated with all of the active therapeutic classes of medications during the course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized clinical trials have demonstrated superior response rates and progression-free survival times with doublet therapy compared with single-agent fluoropyrimidine therapy [10 -12]. The monoclonal antibodies bevacizumab and cetuximab have contributed further improvements in the response rate and overall survival when combined with chemotherapy [13,14]. A meta-analysis conducted by Grothey et al [15] indicated that patients with advanced CRC received the greatest survival benefit when treated with all of the active therapeutic classes of medications during the course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This phase III study compared conventional FOLFIRI chemotherapy with the FOLFIRI chemotherapy combined with cetuximab. Preliminary efficacy results were presented at ASCO 2007(Van Cutsem et al 2007. In 1198 patients of the Intent-To-Treat population, the objective response rate was significantly higher with addition of cetuximab (47% vs. 39%, P = 0.038), and the progression-free survival was also longer (8.9 vs. 8 months, P = 0.048).…”
Section: Kras and Efficacy Of Cetuximab: Preliminary Resultsmentioning
confidence: 99%
“…This observation has also been described in studies with EGFR inhibitors in colorectal, lung, pancreatic, and head and neck cancer. 33,[38][39][40] Preliminary studies examining whether patients should be treated with higher drug levels until experiencing a clinically significant rash have been reported in the context of colorectal cancer, and suggest improved efficacy with the use of the ''dose-to-rash'' strategy. 41 However, this remains to be established in larger Phase 3 studies and in other tumor types.…”
Section: Discussionmentioning
confidence: 99%